Accurate and Practical Calibration of Multiple Pan-Tilt-Zoom Cameras for Live Broadcasts - Masanori Kano; Hidehiko Okubo; Masaki Takahashi; Kensuke Ikeya; Kensuke Hisatomi; Tomoyuki Mishina (IEEE Access, 2020)
We aim to realize novel services for live broadcasts, including visualizing the 3D position of a subject, using multiple pan-tilt-zoom (PTZ) cameras. For this purpose, a camera calibration technique with high accuracy over a wide pan-tilt-zoom range and high operability is required. Herein, we propose an accurate and practical method to calibrate multiple PTZ cameras for live broadcasts. This method models the PTZ camera system and accurately pre-estimates unknown parameters in the model. After the pre-estimation, accurate camera parameters can be calculated in real time using the pan-tilt angles and zoom values acquired from the sensors in the camera system. The proposed method accurately estimates the unknown parameters for a high-magnification zoom lens by making repeated initial guesses and nonlinear optimizations for high accuracy, and consists of a two-stage camera calibration for operability. We demonstrated the effectiveness of the proposed method by conducting experiments on computer graphics data and real data. We also applied it to a live sports graphics system.